A Geriatrician's Guide to Hearing Loss. Issue 5 (9th March 2021) - Jilla, Anna M.; Reed, Nicholas S.; Oh, Esther S.; Lin, Frank R.
Abstract: The high prevalence of hearing loss among older adults creates a perception that it is simply a benign consequence of aging, which leads to unaddressed communication needs. Strategies to address hearing loss as part of routine clinical care are pertinent to the geriatric care setting where hearing loss is prevalent in two out of every three patients 70 years and older. Our objectives are to briefly discuss the pathophysiology of hearing loss, describe the epidemiologic prevalence and impact, identify statutory barriers facing older adults in accessing hearing care, discuss current progress on legislation to address accessibility issues, and provide actionable strategies for addressing hearing loss as a barrier to effective communication. Simple steps can be taken to improve hearing care accessibility for older adults with hearing loss and can optimize understanding in daily communication, re‐engage patients in being actively involved in their care, and promote patient autonomy in informed decision‐ making.